Post Disaster Reconstruction in Sindhupalchok after Earthquake 2015: Problem and Prospects - Dangi, Top Bahadur (Journal of APF Command and Staff College, 2018)
This research has been carried out amidst of delay accomplishment of Post Disaster Reconstruction (PDR) to find out the problem and prospect of PDR in Sindhupalchowk. All data has been collected from primary and secondary source. Data from secondary source, National Reconstruction Authority, field visit and FGD has been incorporated as par requirement. Qualitative and quantitative data analysis was the main instrument for this study. The frequency, intensity, severity and ramification of disaster are increasing day by day. The number of dead, injured, displaced and damage is also increasing. Disaster is becoming a great threat for human, social, economic and environmental sustainability and for development. PDR is a program of recovery and rehabilitation phase of disaster management where actions taken to restore and improve pre-disaster living condition of affected communities. PDR is usually slow, expensive, complex and controversial issue which gives positive result only if it is carried out in well managed, transparent and participatory approach. Build back better and linking reconstruction with development and economic activities are the fundamental and essential element of successful reconstruction. Socioeconomic condition of people can be enhanced by adopting appropriate measure in PDR. After earthquake 2015, NRA has been established and is working all over the affected area of Nepal. Sindhupalchok is one of the most affected districts by earthquake 2015, where NRA has launched its reconstruction program which is in progress but is not as successful as expected before. Political instability, bureaucratic inefficiency, lack of sufficient finance, trained human resource and construction material, poverty and noncompliance of people are major reason behind the delay accomplishment of PDR. Government has to execute its policy strictly and people also have to be cooperative towards the government policy and should reconstruct their house according to the guidelines of NRA within given timeframe.